Evaluation of an online education module designed to reduce stillbirth. (7th June 2021) - Andrews, Christine; Meredith, Natasha; Seeho, Sean; Weller, Megan; Griffin, Alison; Ellwood, David; Middleton, Philippa; Jennings, Belinda; Flenady, Vicki
Abstract : Background: The Safer Baby Bundle (SBB) eLearning is an online education module that addresses practice gaps in stillbirth prevention in Australia. It provides healthcare professionals with evidence‐based resources for: smoking cessation; fetal growth restriction; decreased fetal movements; maternal safe going‐to‐sleep position; and timing of birth for women with risk factors for stillbirth. Aims: To determine whether participants' reported knowledge and confidence in providing care designed to reduce stillbirth changed following completion of the module. To assess the module's suitability and acceptability, and participants' reported likelihood to change practice. Materials and methods: In‐built surveys undertaken pre‐ and post‐eLearning module assessed participant knowledge and confidence, module suitability and acceptability, and likelihood of practice change using Likert items. Responses were dichotomised. Differences pre‐ and post‐module were tested using McNemar's test and differences by profession were examined using descriptive statistics and Pearson's χ 2 test. Results: Between 15 October 2019 and 2 November 2020, 5223 participants across Australia were included. Most were midwives (82.0%), followed by student midwives (4.6%) and obstetricians (3.3%). Reported knowledge and confidence improved in all areas ( P  < 0.001). Post‐module 96.7–98.9% 'agreed' they had a sound level of knowledge and confidence across all elements of the SBB. Over 95% of participants agreed that the module was helpful and relevant, well organised, and easy to access and use. Eighty‐eight percent reported they were likely to change some aspect of their clinical practice. Conclusions: The SBB eLearning module is a valuable education program that is well‐received and likely to result in improvements in practice.